Isolation and Characterization of Compounds from Ochreinauclea maingayi (Hook. f.) Ridsd. (Rubiaceae) with the Aid of LCMS/MS Molecular Networking - Norfaizah Osman; Azeana Zahari; Hazrina Hazni; Wan Nurul Nazneem Wan Othman; Nurulfazlina Edayah Rasol; Nor Hadiani Ismail; Pierre Champy; Mehdi A. Beniddir; Marc Litaudon; Khalijah Awang (Separations, 2023)
Phytochemical investigation of the dichloromethane crude extract from the bark of Ochreinauclea maingayi with the aid of LCMS/MS-based molecular networking guided the isolation and accelerated the elucidation of known and new indole alkaloids. The molecular networking analysis produces two main clusters, along with 41 non-prioritized clusters and self-loop nodes. Each cluster has several nodes which depict the fractions contained within those nodes. An implementation of a fraction mapping for each node represents the molecular weight and key fragment data of each compound. From the analysis of each cluster and node, we can deduce the indole alkaloids are the scaffold of interest. Indole scaffold can be found between F5 and F10 that contain several types of indole alkaloids. In total, we have successfully purified nine indole alkaloids, including 9H-β-carboline-4-carboxylate 2, norharmane 3, harmane 4, naucledine 10, neonaucline 15, 1,2,3,4-tetranorharmane-1-one 16, naulafine 19, cadambine 9, and a new monoterpene indole alkaloid dihyrodeglycocadambine 7 from F5 to F10 using a chromatographic technique. Their structures were confirmed by 1D-NMR, 2D-NMR, UV, IR, LCMS, and MS2LDA. Several clusters and nodes contain ions that could not be annotated, suggesting that they may possess novel compounds that are yet to be discovered.